Histopathology of extra-pulmonary tuberculosis at pathology lab of Patan Hospital, Nepal (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Tuberculosis is a common condition in underdeveloped countries, with approximately 100,000 cases in Nepal today. Tuberculosis is the 6th leading cause of death in Nepal. This study aims to find out the Extra Pulmonary Tuberculosis in the specimen received in the pathology lab.Method: This is a retrospective descriptive study of the histopathology database of Extra Pulmonary Tuberculosis at the pathology lab of Patan Hospital, Nepal from 2012 to 2019. Data were analyzed for prevalence, cite, and pathology details. Ethical approval was obtained from the Institutional review committee of Patan Hospital.Result: There were 300(1%) Extra Pulmonary Tuberculosis out of 29629 specimens. The majority 170(57%) were from the lymph nodes, 36(12%) skin, followed by intestine and urogenital each 28 and 26(9%). Male to female ratio was 2:3 (n=116, 39% vs n=184, 61%). The most common age group was 20-39 years comprising 194(64%). Granuloma was present in 288(96%), and 21(7%) tested positive for Acid Fast Bacilli.Conclusion:  Among the Extra Pulmonary Tuberculosis, more than half of them had tubercular lymphadenitis with granuloma present in the majority.